2015
DOI: 10.1038/srep08250
|View full text |Cite
|
Sign up to set email alerts
|

Associations of PI3KR1 and mTOR Polymorphisms with Esophageal Squamous Cell Carcinoma Risk and Gene-Environment Interactions in Eastern Chinese Populations

Abstract: Single nucleotide polymorphisms (SNPs) in the PI3K/PTEN/AKT/mTOR signaling pathway may contribute to carcinogenesis. We genotyped five potentially functional PIK3R1 and mTOR SNPs in 1116 esophageal squamous cell cancer (ESCC) patients and 1117 cancer-free controls to assess their associations with ESCC risk. We observed no association with ESCC risk for any of the selected SNPs. However, the combined analysis of these SNPs revealed that subjects with one-to-three risk genotypes had an increased ESCC risk. Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…Two studies have assessed associations between functional SNPs in mTOR gene and risk of ESCC in Chinese populations. They genotyped several mTOR SNPs in ESCC patients and found a significantly altered risk of ESCC associated with mTOR rs1883965 and mTOR rs2295080 [3536]. An early study identified seven SNPs of PI3K/PTEN/AKT/mTOR pathway in patients with advanced ESCC treated with 5-Fu, cisplatin or paclitaxel, and explored the association between clinical outcome and genetic variations.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have assessed associations between functional SNPs in mTOR gene and risk of ESCC in Chinese populations. They genotyped several mTOR SNPs in ESCC patients and found a significantly altered risk of ESCC associated with mTOR rs1883965 and mTOR rs2295080 [3536]. An early study identified seven SNPs of PI3K/PTEN/AKT/mTOR pathway in patients with advanced ESCC treated with 5-Fu, cisplatin or paclitaxel, and explored the association between clinical outcome and genetic variations.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out genotyping on the platform of the TaqMan real-time PCR method on a 7900 Sequence Detection System (Applied Biosystems, Foster City, CA). The technique details were described previously 40, 41, 42. Quality control was strictly executed; four duplicate positive controls and four negative controls (omitting DNA template) were loaded, along with samples in each of the 384-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous epidemiologic investigations and researches have focused on the epidemiological etiology to explain the rapid increase of this lethal cancer 8 9 10 . Tobacco use, alcohol consumption and mutations of enzymes that metabolizing alcohol have been the primary causes of ESCC, however, alcohol consumption is not considered as a risk factor for EAC 11 12 13 .…”
mentioning
confidence: 99%